2003
DOI: 10.1017/s0952523803202042
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regenerative activity in mammalian retinal bipolar cells: Roles of multiple subtypes of voltage-dependent Ca2+ channels

Abstract: Patch-clamp recordings were used to investigate the properties of the regenerative activity in acutely isolated bipolar cells from the rat retina. Spontaneous, pacemaker-like membrane potential oscillations were observed in all rod bipolar cells and the majority of cone bipolar cells. The waveform of the regenerative potential was stereotypical but distinct among different bipolar cell groups, especially between rod and cone bipolar cells. The spontaneous activity was completely blocked by Co2+, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
5
37
0
Order By: Relevance
“…Glutamatergic waves are mediated by glutamate release from bipolar cells (Firl et al , 2013; Akrouh & Kerschensteiner, 2013), however which aspects of the circuit control burst properties and the frequency of waves are not yet identified. In the retina, T-type channels have been described in bipolar cell terminals and retinal ganglion cells (Ma & Pan, 2003; Pan et al , 2001; Lee et al , 2003; Hu et al , 2009; Cui et al , 2012; Sargoy et al , 2014). Hence, future experiments will be necessary to determine whether these changes are due to changes in the pacemaking or release properties from bipolar cells or in the excitability of RGCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamatergic waves are mediated by glutamate release from bipolar cells (Firl et al , 2013; Akrouh & Kerschensteiner, 2013), however which aspects of the circuit control burst properties and the frequency of waves are not yet identified. In the retina, T-type channels have been described in bipolar cell terminals and retinal ganglion cells (Ma & Pan, 2003; Pan et al , 2001; Lee et al , 2003; Hu et al , 2009; Cui et al , 2012; Sargoy et al , 2014). Hence, future experiments will be necessary to determine whether these changes are due to changes in the pacemaking or release properties from bipolar cells or in the excitability of RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…A critical component of the network mediating waves and a primary source of depolarizing input to RGCs is glutamate release from bipolar cells (Firl et al , 2013; Akrouh & Kerschensteiner, 2013). In the adult retina, bipolar cells exhibit unstable membrane potentials and their spontaneous depolarizations are mediated by low-voltage activated T-type calcium channels (Ma & Pan, 2003; Cueni et al , 2009; Sargoy et al , 2014; Puthussery et al , 2014) that are expressed in subsets of bipolar cells (Pan et al , 2001; Singer & Diamond, 2003) and of ganglion cells (Sargoy et al , 2014). The isoform α1 H (Ca V 3.2) of the T-type Ca 2+ channel (Cueni et al , 2009) localizes to cone bipolar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The bipolar cells code neuronal signals by a depolarization of their membrane voltage. If an incoming depolarization reaches voltage gated Ca 2+ channels located at the axon terminal of the bipolar cells further signalling to amacrine and ganglion cells is initiated (Ma and Pan, 2003;Pan et al, 2001;Satoh et al, 1998). Numerical simulations have shown that subretinally applied electric fields can also depolarize the axon terminal of bipolar cells Gerhardt et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…It is generally accepted that retinal BCs respond to light stimulation with graded potentials (Werblin and Dowling, 1969;Kaneko, 1973). However, recent studies show that some types of BCs have the ability to generate Ca 2ϩ and/or Na ϩ spikes [Ca 2ϩ spikes: Burrone and Lagnado (1997), Zenisek and Matthews (1998), Protti et al (2000), Hull et al (2006), Palmer (2006), and Hu et al (2009); Na ϩ spikes: Ma et al (2005); Ca 2ϩ and Na ϩ spikes: Ma and Pan (2003)]. As Ca 2ϩ and/or Na ϩ spikes in BCs are much slower in time course than Na ϩ spikes in amacrine cells, it is intriguing to know how the electrically coupled BCs with such active membrane properties behave in the retina.…”
Section: Introductionmentioning
confidence: 99%